Odpowiedź :
Odpowiedź:
(3x + 5)/6 - (6x + 2)/4 - 2 = 0 | * 12
2(3x + 5) - 3(6x + 2) - 24 = 0
6x + 10 - 18x - 6 - 24 = 0
- 12x - 20 = 0
- 12x = 20
12x = - 20
x = - 20/12 = - 1 8/12 = - 1 2/3
3x/4 - (100 - 5x)/6 = 29 | * 12
3 * 3x - 2(100 - 5x) = 348
9x - 200 + 10x = 348
19x = 348 + 200 = 548
x = 548/19 = 28 16/29
(x - 3)/4 + (x - 4)/3 = (x - 5)/2 - (x - 4)/8 | * 24
6(x - 3) + 8(x - 4) = 12(x - 5) - 3(x - 4)
6x - 18 + 8x - 32 = 12x - 60 - 3x + 12
14x - 50 = 9x - 48
14x - 9x = - 48 + 50
5x = 2
x = 2/5
(2x + 3)/5 + (4x - 1)/10 = x/2 | * 20
4(2x + 3) + 2(4x - 1) = 10x
8x + 12 + 8x - 2 = 10x
16x + 10 = 10x
16x - 10x = - 10
6x = - 10
x = - 10/6 = - 1 4/6 = - 1 2/3